COMPOSITIONS AND METHODS FOR THE TREATMENT OF ZELLWEGER SPECTRUM DISORDER (2017)
Provided herein are methods of treating Zellweger spectrum disorder (ZSD) in a subject in need thereof or improving peroxisome assembly in a cell in need thereof comprising administering to the subject a therapeutically effective amount of Compounds of Formula I or II.